Numerical investigation of trapezoidal grooved microchannel heat sink using nanofluids - Kuppusamy N.R.; Mohammed H.A.; Lim C.W. (2023)
A numerical investigation is performed to study the thermal and flow fields in a trapezoidal grooved microchannel heat sink (TGMCHS) using nanofluids. The governing and energy equations are solved using the finite volume method. The influence of the geometrical parameters such as the width, depth and pitch of the groove on the thermal performance of TGMCHS was examined. The effects of different nanoparticle types, volume fraction, particle diameter and base fluid at different Reynolds numbers are also studied. It is found that the increment of the maximum width 'a' and reduction of the minimum width 'b' of the trapezoidal groove gives the maximum thermal performance and this implies that the triangular shape would be favorable compared to rectangular shape MCHS. It is inferred that Al2O3-H2O had the highest thermal performance with 0.04 volume fraction and 25 nm particle diameter. 2013 Elsevier B.V. All rights reserved.